Local microscopic properties and annealing effect of Rb0.85Fe1.9Se2 single crystals. (6th March 2017) - Szymański, K; Olszewski, W; Satuła, D; Matwiejczyk, A; Gawryluk, D J; Krztoń-Maziopa, A; Puźniak, R; Wiśniewski, A
Abstract: Investigation of mesoscopically phase-separated Rb0.85 Fe1.9 Se2 single crystals has been performed and two iron sites: nonmagnetic and magnetic ones, were observed by Mössbauer spectroscopy. The softening of the nonmagnetic one, having clearly more soft dynamics, was found to be gained further by the annealing of the single crystals at phase separation temperature, T p, leading to the reduction of size of initially separated domains and their more homogenous distribution in the tetragonal matrix of the studied sample. The magnetic Fe sites of Rb0.85 Fe1.9 Se2 show strong magnetic texture, indicating the perpendicular to the ab -plane orientation of the iron magnetic moments. It was found that the annealing at T p causes a systematic decrease of the isomer shift of the doublet by 0.02(1) mm s −1 .